Central European Woolly Mammoth Population Dynamics: Insights from Late Pleistocene Mitochondrial Genomes - Fellows Yates, James A; Drucker, Dorothée G; Reiter, Ella; Heumos, Simon; Welker, Frido; Münzel, Susanne C; Wojtal, Piotr; Lázničková-Galetová, Martina; Conard, Nicholas J; Herbig, Alexander; Bocherens, Hervé; Krause, Johannes (Scientific reports, 2017)
The population dynamics of the Pleistocene woolly mammoth (Mammuthus primigenius) has been the subject of intensive palaeogenetic research. Although a large number of mitochondrial genomes across Eurasia have been reconstructed, the available data remains geographically sparse and mostly focused on eastern Eurasia. Thus, population dynamics in other regions have not been extensively investigated. Here, we use a multi-method approach utilising proteomic, stable isotope and genetic techniques to identify and generate twenty woolly mammoth mitochondrial genomes, and associated dietary stable isotopic data, from highly fragmentary Late Pleistocene material from central Europe. We begin to address region-specific questions regarding central European woolly mammoth populations, highlighting parallels with a previous replacement event in eastern Eurasia ten thousand years earlier. A high number of shared derived mutations between woolly mammoth mitochondrial clades are identified, questioning previous phylogenetic analysis and thus emphasizing the need for nuclear DNA studies to explicate the increasingly complex genetic history of the woolly mammoth.
Keywords: mitochondriální DNA; DNA, Ancient; DNA, Mitochondrial; zkameněliny; haplotypy; Extinction, Biological; fylogeneze; Mammoths; Sequence Analysis, DNA; Phylogeny; sekvenční analýza DNA; Europe; extinkce biologická; Haplotypes; Fossils; genom mitochondriální; proteomika; Evropa; Population Dynamics; Genome, Mitochondrial; Animals; starobylá DNA; populační dynamika; zvířata; Proteomics; mamuti